Cs+ substituted SrZnFe2O4 nanoparticles: analysis of structural, morphological and electrical behavior - Suriani Abu Bakar (Tanjung Malim, 2024)
Cs+ substituted SrZnFe2O4 nanoparticles: analysis of structural, morphological and electrical behavior by Suriani Abu Bakar